OVERCOMING SLOW LEARNERS’ CHALLENGES: THE IMPORTANCE OF PSYCOSOCIAL SUPPORT IN THE EDUCATIONAL ENVIRONMENT - Paresti, Suci Paresti; Subagyo, Tatang; Ariantoni, Ariantoni; Mudhari, Marga Surya; Suherman, Dan (JURNAL EDUSCIENCE, 2024)
Slow learners (SL) often face challenges in academic and social adaptation, thus requiring structured psychosocial support. This study aims to analyze the implementation of psychosocial support for SL at SDN Pisangan Timur 11 Jakarta Timur. Using a qualitative approach with a case study method, data were collected through classroom observations, in-depth interviews, and focus group discussion (FGD) involving teachers, parents, and students. The findings indicate that psychosocial support at SDN Pisangan Timur 11 comprises three dimensions: emotional, support, instructional support, and social support. Emotional support, such as motivation and praise, helps enhance SL’s self-confidence. Instructional support involves adjusting instructions, repetition, and strategic seating arrangements. Social support is facilitated through peer tutoring, which effectively improves SL’s academic understanding and social adaptation. Challenges include limited focus, high dependency on teachers and peers, and insufficient teacher training. This study highlights the novel finding that peer tutors can serve as a strategic element in supporting SL in inclusive education setting.Keywords: slow learners, psychosocial support, inclusive education, peer tutoring, instructional strategies